Experimental investigation on the mechanical behavior of polyvinyl alcohol fiber recycled aggregate concrete under triaxial compression. (3rd October 2022) - Chen, Yuliang; Li, Peize; Ye, Peihuan; Li, Hong; Liang, Xin
Highlights: Triaxial compression tests were performed on PFRAC and the results are discussed. Variation in replacement rate affects peak stress, but not by more than 20%. The crack inhibition mechanism of PF under triaxial compression was revealed. Triaxial strength calculation formula of PFRAC is suggested. Abstract: The development of engineering construction has caused a series of resource shortages and environmental pollution problems, and the use of recycled aggregate concrete (RAC) technology to solve the problem has been proved to be an effective measure. At present, fiber recycled aggregate concrete (FRAC) has been widely studied and applied, in addition, some concrete structures in engineering will be under triaxial compression. Thus, studying the mechanical performance of polyvinyl alcohol fiber recycled aggregate concrete (PFRAC) under triaxial compression is crucial. In this work, 168 cylindrical PFRAC specimens of 100 mm (diameter) × 200 mm (height) were designed and tested under triaxial compression. The failure modes of specimens were observed, and the stress–strain curves, peak stress, peak strain, and elastic modulus were obtained. The experimental results show that with the increase of lateral confining pressure, the failure mode of the specimen changes from longitudinal splitting failure to oblique shear failure. When the lateral confining pressure reaches 15 MPa, serrated micro-cracks appear on the specimen surface. With the increase of the replacement rate, the peak stress of the specimen gradually decreases, but the decrease is not more than 20 %. Lateral confining pressure can significantly improve peak stress and peak strain of specimens. Compared with the triaxial compression specimen, PF has a better improvement effect on the elastic modulus of the uniaxial compression specimen. Based on test data and some related theories, the calculation formula of PFRAC triaxial compressive strength under different fiber contents is proposed, which can provide reference for the further research and practical engineering application of RAC.